SINGKRONISASI PENYULANG INCOMING GH TERBAN UNTUK PENINGKATAN KEHANDALAN DAN PERBAIKAN SUSUT TEKNIK PADA PT. PLN (PERSERO) ULP KUALA SIMPANG - Alfaoqi, Muhammad (Power Elektronik : Jurnal Orang Elektro, 2024)
In channeling electrical energy from the power plant to the customers, a distribution system called the Electric Power Distribution System is required. The Electric Power Distribution System consists of high voltage lines, medium voltage lines, and low voltage lines. In the medium voltage system, the electrical network is designed in such a way to achieve reliability and good voltage quality when it reaches the customers. The aim of this journal is to analyze the operating pattern of the medium voltage network at PT PLN (Persero) ULP Kuala Simpang at the Terban Grounding Substation, by synchronizing 2 incoming feeders, namely feeder TC05 and TC12, through the coupling cubicle of the Terban Grounding Substation. The synchronization of these feeders aims to improve system reliability and reduce technical losses on the feeder side.